2019
DOI: 10.1155/2019/8071619
|View full text |Cite
|
Sign up to set email alerts
|

On-the-Scene Hyaluronan and Syndecan-1 Serum Concentrations and Outcome after Cardiac Arrest and Resuscitation

Abstract: Background. It is not predictable which patients will develop a severe inflammatory response after successful cardiopulmonary resuscitation (CPR), also known as “postcardiac arrest syndrome.” This pathology affects only a subgroup of cardiac arrest victims. Whole body ischemia/reperfusion and prolonged shock states after return of spontaneous circulation (ROSC) may both contribute to this devastating condition. The vascular endothelium with its glycocalyx is especially susceptible to initial ischemic damage an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 32 publications
(47 reference statements)
0
15
0
Order By: Relevance
“…227 However, two studies have reported elevations in sdc-1 and HA in patients with cardiovascular disease. 159,184 Support for compensatory reaction(s) can be inferred from an in vivo study of the glycocalyx in sdc-1 knock-out (KO) mice where Savery et al used micro-particle velocimetry to determine the presence of a hydrodynamically significant cell surface layer. 249 They observed no difference in wild-type vs. sdc-1 KO mice and concluded that sdc-1 was not necessary for the existence of an endothelial glycocalyx.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…227 However, two studies have reported elevations in sdc-1 and HA in patients with cardiovascular disease. 159,184 Support for compensatory reaction(s) can be inferred from an in vivo study of the glycocalyx in sdc-1 knock-out (KO) mice where Savery et al used micro-particle velocimetry to determine the presence of a hydrodynamically significant cell surface layer. 249 They observed no difference in wild-type vs. sdc-1 KO mice and concluded that sdc-1 was not necessary for the existence of an endothelial glycocalyx.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in one study assessment of the glycocalyx by SDF imaging showed no significant difference in glycocalyx dimensions between patients with and without cardiovascular disease 227 . However, two studies have reported elevations in sdc‐1 and HA in patients with cardiovascular disease 159,184 . Support for compensatory reaction(s) can be inferred from an in vivo study of the glycocalyx in sdc‐1 knock‐out (KO) mice where Savery et al used micro‐particle velocimetry to determine the presence of a hydrodynamically significant cell surface layer 249 .…”
Section: Discussionmentioning
confidence: 99%
“…Syndecan-4 is shed by MMP-9 in a TNF-α-dependent manner [ 49 ]. MMPs are also able to cleave chondroitin sulfate [ 50 ].…”
Section: Mechanisms Of Endothelial Glycocalyx Damagementioning
confidence: 99%
“…Pathological damage of the glycocalyx occurs in response to mechanical cellular stress, endotoxins, inflammatory mediators, atrial natriuretic peptide, ischemia/reperfusion injury, free oxygen radicals, and hyperglycemia, as well as the novel coronavirus disease 2019 (COVID-19) [ 49 , 66 ]. Degradation of the glycocalyx results in the shedding of some of its components in the blood flow (hyaluronic acid, heparan sulfate, syndecan-1 and 4, and glypicans), and often they correlate with the severity of particular diseases [ 50 , 67 ].…”
Section: Glycocalyx Dysfunction Conditionsmentioning
confidence: 99%
“…Experimental models of ischaemia/reperfusion and hypoxia/reoxygenation showed that myocardial hypoxia and ischaemia induce an early ESL degradation [3], with purin signalling and perivascular mast cell-derived heparanase being a possible contributing factor [4]. Increased blood levels of shed ESL components such as syndecan-1, hyaluronan and heparan sulphate can be detected in successful cardiopulmonary resuscitation after cardiac arrest, trauma and sepsis and may serve as an early predictor of adverse clinical outcome [5][6][7]. Soluble components of the endothelial glycocalyx may act as damage associated molecular patterns (DAMPs), further augmenting inflammation and tissue damage.…”
Section: Introductionmentioning
confidence: 99%